Clear messages to the European public? The language of European Commission press releases 1985–2020 - Christian Rauh (Journal of European Integration, 2022)
The public politicisation of European integration indicates a growing demand for public communication of supranational politics. This paper highlights that the messages the European Commission sends to its citizens do not meet this demand. A text analysis of almost 45,000 press releases the Commission has issued during 35 years of European integration rather indicates an extremely technocratic style of communication. Benchmarked against large samples of national executive communication, public political media, and scientific discourse, the Commission used and notably continues to use very complex language, specialized jargon, and a nominal style that obfuscates political action. This appears disadvantageous in a politicized context and more research on the reasons for this apparent communication deficit is needed.
Keywords: 320; European commission; political communication; politicisation; text analysis; press releases